Histopathological Study of Ovarian Tumors at a Tertiary Care Hospital of Central Nepal - Goyal, Binita; Rao, T Sheshagiri; Regmi, Himanshu (Journal of College of Medical Sciences-Nepal, 2019)
Background: Ovarian tumors are histogenetically varied and complex tumors spanning all age groups. They account for 30% of all gynaecologic cancers. Malignant tumors carry a high mortality due to its late detection and ineffective screening programs. Current study aims at finding association between age at presentation and size of tumor with behavior of tumors and also association between category of tumor and age at presentation. Methods: This Hospital record based cross-sectional (historical) study was carried out on 158 cases of ovarian tumors received in Department of Pathology, College of Medical Sciences and Teaching Hospital during a time period of five and a half years from January 2012 to June 2017. Results: Age of the patients ranged from 12 to 88 years with maximum cases 96 (60.8%) in 20 – 40 years age group. The mean ±SD of age was 36.6±14.4 years. Majority of the cases 137 (86.7%) were benign. Sixteen (10.1%) cases were malignant and 5 (3.2%) cases were borderline. Majority of both benign and malignant cases were seen in 20 – 40 years age group. Size of the tumors ranged from 2 – 30 cm with mean±SD of 9.9±5.0 cm and maximum 93 (58.9%) cases in the size range of 5 – 10 cm. Majority of both benign and malignant tumors were in the size range of 5 – 10 cm. There was no association of age at presentation and size of tumor with behavior of tumor (p > 0.05). Sevety five (47.5%) cases were germ cell tumors, 72 (45.6%) cases were surface epithelial-stromal tumors, 9 (5.7%) cases were sex cord-stromal tumors, 1 (0.6%) was bilateral with surface epithelial tumor in right ovary and germ cell tumor in left ovary and 1 (0.6%) case was soft tissue tumor not specific to ovary. Majority of cases of germ cell tumors were seen below 40 years age whereas significant proportion of surface epithelial-stromal tumors was seen after 40 years with significant association between category and age at presentation (p < 0.05). Most common histopathological diagnosis overall was dermoid cyst in 43.7% cases. Conclusions: Benign ovarian tumors were more common than malignant ones. Malignancy was seen in all age groups and in any size tumor. Surface epithelial-stromal tumors and germ cell tumors were roughly equal in frequency with slight predominance of latter. Germ cell tumors were common in younger whereas surface epithelial-stromal tumors were more common in older individuals. Histopathological examination in any ovarian tumor at any age with any size is mandatory.